Perbedaan Pengetahuan, Sikap, dan Persiapan Kegawatdaruratan Obstetri Ibu Hamil Sebelum dan Sesudah Pendampingan oleh Kelompok Perempuan “Bundo” - Devi Syarief; Desi Wildayani; Winda Listia Ningsih (Politeknik Negeri Jember, 2022)
Maternal mortality remains a major public health challenge worldwide. To prevent maternal mortality, further efforts are focused on empowering better communities, empowering women and strengthening the health care system, including the quality of emergency obstetric services. The purpose of this study was to determine differences in knowledge, attitudes, and preparation for emergency obstetrics in pregnant women before and after mentoring groups of women. This type of research is quantitative with a quasi-experimental pre-posttest design with one group design. The research was carried out in Kurao Pagang Village, Padang City, carried out for 3 months, starting from August to October 2021. The research population was pregnant women in the 1st, 2nd and 3rd trimesters in the working area of ​​Kurao Pagang Village, Padang City. The total population is 24 people. The entire population will be used as the research sample (total population). The data was processed using the Wilcoxon test. The results of the study showed that there was a significant difference between the scores before and after assistance was given to pregnant women by a group of women with a p value = 0.000 regarding knowledge, attitudes and preparation for obstetric emergencies. It is hoped that this mentoring program by women's groups will continue to be implemented and can also be applied to other areas. This community empowerment should also be a priority program for the authorities in order to reduce the maternal mortality rate in Indonesia.